Comparative evaluation of pressure massage at Hegu point versus Kunlun–Taixi pressure points on physiological parameters and crying duration induced by intramuscular vitamin K injection in premature infants: A clinical trial study - Seyedeh Fatemeh Ghasemi; Atefeh Jadidi; Fatemeh Valizadeh; Rasool Mohammadi; Fatemeh Janani; Hanieh Goodarzi (حیات)
Background & Aim: Intramuscular injections represent a painful procedure for premature infants. This study aimed to compare the effects of pressure massage at Hegu point versus Kunlun–Taixi pressure points on pulse rate, arterial oxygen saturation, and crying duration following intramuscular injection of vitamin K in premature infants. Methods & Materials: A randomized, single-blind clinical trial was conducted on 100 premature infants admitted to the neonatal intensive care unit between 2020 and 2021. Participants were selected through convenience sampling and then randomly assigned into four groups of 25 individuals each: Hegu point massage, Kunlun–Taixi points simultaneous massage, placebo and control. Prior to the vitamin K injection, the intervention groups received targeted pressure point massage, the placebo group received nasal tip massages, and the control group received standard care. Pulse rate, arterial oxygen saturation, and crying duration were recorded before, during and after the intramuscular injection using a pulse oximeter and chronometer. Data were analyzed using two-way repeated measures analysis of variance in SPSS software version 24. Results: Significant differences were observed in average pulse rate (P=0.013) and average arterial oxygen saturation (P=0.028). The group receiving simultaneous massage at Kunlun–Taixi points exhibited the lowest mean pulse rates during (149.24±7.78) and after (144.16±8.64) the injection, as well as the highest mean arterial oxygen saturation percentages during (88.36±9.37) and after (88.04±8.33) the injection. Conclusion: Simultaneous massage of Kunlun–Taixi pressure points reduced changes in pulse rate and arterial oxygen saturation induced by intramuscular injection in premature infants. It is recommended to use this simple and low-priced method to reduce the physiological responses to injection-related pain in premature newborns. Clinical trial registry: IRCT20210630051743N1